Thornwaldt Cyst. A Case Report - Salazar Minaya, Ray (2021)
We present the case of a 49-year-old female patient attending the otorhinolaryngology service with a 3-month history of pain and neck rigidity plus instability. A contrast MRI of the posterior fossa revealed a nodular lesion in the nasopharynx compatible with a Thornwaldt cyst. A nasal endoscopy confirmed the diagnosis. Excision of the cyst under trans nasal endoscopy was performed. Instability persisted but neck pain and neck rigidity improved. We carried-out a literature review.